In vitro Evaluation of 2-/3-Alkoxyphenylcarbamic Acid Esters Containing N-Arylpiperazine Moiety Against Some Nontuberculous Mycobacteria (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Abstract not availableDhaka Univ. J. Pharm. Sci. 14(2): 231-234, 2015 (December)